If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 55x = 333 Solving 6 + 55x = 333 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 55x = 333 + -6 Combine like terms: 6 + -6 = 0 0 + 55x = 333 + -6 55x = 333 + -6 Combine like terms: 333 + -6 = 327 55x = 327 Divide each side by '55'. x = 5.945454545 Simplifying x = 5.945454545
| -10(0)+5y=-50 | | log^4(8x)=6 | | 2x^3+50x^2=0 | | 7(3d-8)= | | 17x^2+16x+4= | | 2(n+5)=4n+10 | | h^3+1=0 | | 2(5x+1)=10x-3 | | m-14=37 | | 1.9q-4.1-4.2q=3.3q-5.1 | | 8-4(x-2)=8 | | 9(x-7)=-18.9 | | 2x+6y=145 | | 4(a+5)=44.8 | | 5(0)-4y=-20 | | 3=5c-8 | | 40+4x-16=13x-12-3x | | 9e-3=79.8 | | (4v-6)(8+b)=0 | | 10+13+16+4x-8=180 | | 5(a+7)=55 | | -4x^3+25x=24 | | 15+20+25+3x-7=180 | | 11=-3x-7 | | ln(x^2)+ln(16x)-2ln(2x)=3 | | 9+9x=54 | | 16-x=12+2x | | 4x/2+12=2 | | 12-7x=-65 | | -13+4x=-39+10x | | -7+6x=-37 | | x^2-54x-232=0 |